Answer:
x=0.450765 or x=−0.950765
Step-by-step explanation:
14x² + 7x - 6
→ Find the product, sum and factors
Product = -6
Sum = 7
Factors = No factors
→ Since there are no factors utilise the quadratic formula
![\frac{-b+-\sqrt{b^{2}-4ac } }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%7Bb%5E%7B2%7D-4ac%20%7D%20%7D%7B2a%7D)
→ List the values of a, b and c
a = 14
b = 7
c= -6
→ Substitute into the formula
![\frac{-7+-\sqrt{7^{2}-4*14*-6} }{2*14}](https://tex.z-dn.net/?f=%5Cfrac%7B-7%2B-%5Csqrt%7B7%5E%7B2%7D-4%2A14%2A-6%7D%20%7D%7B2%2A14%7D)
→ Simplify
x=0.450765 or x=−0.950765
Step-by-step explanation:
![\tt{30.16 = 17.56 + 5x}](https://tex.z-dn.net/?f=%20%5Ctt%7B30.16%20%3D%2017.56%20%2B%205x%7D%20)
Swap the sides of the equation :
⤑ ![\tt{17.56 + 5x = 30.16}](https://tex.z-dn.net/?f=%20%5Ctt%7B17.56%20%2B%205x%20%3D%2030.16%7D)
We want to remove the 17.56 first.
Since the original equation is 17.56 , we are going to use the opposite operation and subtract 17.56 from both sides :
⤑ ![\tt{5x + 17.56 - 17.56 = 30.16 - 17.56}](https://tex.z-dn.net/?f=%20%5Ctt%7B5x%20%2B%2017.56%20-%2017.56%20%3D%2030.16%20-%2017.56%7D)
Simplify. 17.56 - 17.56 = 0 on the left. 30.16 - 17.36 = 12.6 on the right.
⤑ ![\tt{5x = 12.6}](https://tex.z-dn.net/?f=%20%5Ctt%7B5x%20%3D%2012.6%7D)
Then, we need to think about how to remove the coefficient 5. Since the opposite of multiplication is division , I am going to divide both sides by 5.
⤑ ![\tt{ \frac{5x}{5} = \frac{12.6}{5}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B5x%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B12.6%7D%7B5%7D%7D%20)
Simplify. 5/5 = 1 on the left and 12.6/5 = 2.52 on the right. So, Our answer is x = 2.52.
![\pink{ \boxed{ \boxed { \tt{Our \: final \: answer : \underline{ \underline{ \bold{ \tt{x = 2.52}}}}}}}}](https://tex.z-dn.net/?f=%20%5Cpink%7B%20%5Cboxed%7B%20%5Cboxed%20%7B%20%5Ctt%7BOur%20%5C%3A%20final%20%5C%3A%20answer%20%3A%20%20%5Cunderline%7B%20%5Cunderline%7B%20%5Cbold%7B%20%5Ctt%7Bx%20%3D%202.52%7D%7D%7D%7D%7D%7D%7D%7D)
Hope I helped ! ♡
Have a wonderful day / night ! ツ
▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁
Note that f(x) as given is <em>not</em> invertible. By definition of inverse function,
![f\left(f^{-1}(x)\right) = x](https://tex.z-dn.net/?f=f%5Cleft%28f%5E%7B-1%7D%28x%29%5Cright%29%20%3D%20x)
![\implies f^{-1}(x)^3 - f^{-1}(x) + 2 = x](https://tex.z-dn.net/?f=%5Cimplies%20f%5E%7B-1%7D%28x%29%5E3%20-%20f%5E%7B-1%7D%28x%29%20%2B%202%20%3D%20x)
which is a cubic polynomial in
with three distinct roots, so we could have three possible inverses, each valid over a subset of the domain of f(x).
Choose one of these inverses by restricting the domain of f(x) accordingly. Since a polynomial is monotonic between its extrema, we can determine where f(x) has its critical/turning points, then split the real line at these points.
f'(x) = 3x² - 1 = 0 ⇒ x = ±1/√3
So, we have three subsets over which f(x) can be considered invertible.
• (-∞, -1/√3)
• (-1/√3, 1/√3)
• (1/√3, ∞)
By the inverse function theorem,
![\left(f^{-1}\right)'(b) = \dfrac1{f'(a)}](https://tex.z-dn.net/?f=%5Cleft%28f%5E%7B-1%7D%5Cright%29%27%28b%29%20%3D%20%5Cdfrac1%7Bf%27%28a%29%7D)
where f(a) = b.
Solve f(x) = 2 for x :
x³ - x + 2 = 2
x³ - x = 0
x (x² - 1) = 0
x (x - 1) (x + 1) = 0
x = 0 or x = 1 or x = -1
Then
can be one of
• 1/f'(-1) = 1/2, if we restrict to (-∞, -1/√3);
• 1/f'(0) = -1, if we restrict to (-1/√3, 1/√3); or
• 1/f'(1) = 1/2, if we restrict to (1/√3, ∞)
X + 47= 147
hope that helps
Answer:
The quotient rule for exponents states that
.
When dividing exponential expressions with the same nonzero base, <u>subtract</u> the exponents.
Step-by-step explanation:
Some rules to solve exponents are:
The quotient rule for exponents states that:
.
When dividing exponential expressions with the same nonzero base, <u>subtract</u> the exponents.